Penguatan Jiwa Profetik Siswa Sekolah Dasar Melalui Penanaman Nilai-Nilai Religius - Istianah (Jurnal Subulana, 2021)
This article describes the cultivation of religious values ??in elementary schools in order to strengthen the prophetic spirit of students. Elementary schools are educational institutions that have a strategic role in instilling religious values ??from an early age in students. The focus of this study includes religious values ??instilled in elementary schools, strategies for inculcating religious values, and obstacles in inculcating religious values ??in elementary schools. Data were obtained through interviews, observations, and documentation studies at SDN Gedungan 01 Blega. The research subjects were principals, classroom teachers, extracurricular teachers, parents/guardians, and purposefully selected students. The results showed that the religious values ??instilled in SDN Gedung 01 Blega include the values ??of discipline, honesty, responsibility, sincerity, tolerance, mutual respect, and care for the environment. The inculcation of religious values ??is integrated in all subjects, school culture, and extracurricular activities. Research also shows that there are internal and external factors that hinder the cultivation of religious values ??for strengthening students prophetic spirit.